Studi Karakteristik dan Faktor-Faktor Downstream User Transportasi Online (Ride Sharing) di Kota Bandung - Rohmat adi prasetyo (Jurnal Wacana Ekonomi, 2018)
Online transportation (ride sharing) is a phenomenon that has developed in the last 5 years. Commonly known as "online taxis" in Indonesia, its appearance is believed to be able to replace public transportation to compete in the public transportation industry. Competition also occurs among other ride-sharing transportation companies such as Gojek with its Gocar feature. Grab with its GrabCar feature, and Uber with its UberX feature. It is necessary to know what factors influence downstream users in using ride sharing transportation as their choice. In addition, the ease of access through the application for downstream users allows them to switch products easily. Therefore, this study aims to look at the characteristics and factors that influence downstream users in choosing alternative ride sharing transportation. Apart from that, it should also be seen how the segment that is the target of each ride sharing company. The data collection method was carried out through a questionnaire with a cluster sampling technique by dividing the respondents based on the district area. Respondents are active users of online transportation (ride sharing) in Bandung. From the distributed questionnaires, 424 questionnaires were obtained which could be processed for the needs of this study using SPSS version 24 data processing tools. Based on the results of the study, there are 3 characteristics of downstream users in using online transportation (ride sharing), namely loyal, hybrid2, and hybrid3. With 6 influencing factors, namely enjoyment, sustainability, social benefits, economic benefits, reputation, and service experience.